PAKELIRAN RINGKAS DENGAN KONSEP PAKELIRAN PADAT SUATU ALTERNATIF PERTUNJUKAN WAYANG SEKARANG DAN MASA DEPAN - S., Sarwanto (Institut Seni Indonesia Surakarta, 2016)
The study is supposed to discuss about pakeliran ringkas and the concept of pakeliran padat asone alternative for the present as well as future forms of wayang performance. The discussionwill be started from the concept of pakeliran padat and its elements of garap that widely influencethe development of wayang performance previously. Pakeliran ringkas with the concept of pakeliranpadat represents a pakeliran that oriented to the duration of three until four hours by eliminatingsome scenes that are supposed unimportant and uses the concept of garap elements ofpakeliran padat namely harmonizing the media and the content equally. Pakeliran ringkas with theconcept of pakeliran padat avoid something that makes the content superficial. Pakeliran ringkaswith the concept of pakeliran padat as an offered alternative is interestingly packed by considering the essence of guidance as well as entertainment for the society.Keywords: alternative, Pakeliran Ringkas, concept of Pakeliran Padat.